Education on the use of organic waste to become environmentally friendly orozeco (organic fertilizer and eco enzym) - Marlinda Marlinda; Mardhiyah Nadir; Faisal Faisal; Muhammad Wisnu Dwi Purwanto; Dhea Permatasari Putri (Community Empowerment, 2023)
Organic waste is an inseparable part of daily activities in the kitchen. So that the people of RT 34 Bengkuring have the desire to learn and produce kitchen products that can be substituted for chemicals and are more economical. In addition, this activity can reduce the amount of waste disposed of at the Waste Disposal Site (TPS). This activity aims to increase public knowledge about waste management and skills in processing organic waste. The methods provided are in the form of training, mentoring and evaluation. After the training, the community can make their own waste processing products and can produce products for household needs and MSME products, such as compost, liquid organic fertilizer, and eco-enzyme.